2013
DOI: 10.1002/poc.3185
|View full text |Cite
|
Sign up to set email alerts
|

A new pH fluorescent molecular switch by modulation of twisted intramolecularcharge transfer with protonation

Abstract: A pH fluorescent molecular switch, BOPIM-dma, a boron 2-(2′-pyridyl) imidazole complex derivatives, was investigated in aqueous system. BOPIM-dma shows weak or no fluorescence in conventional solvents due to twisted intramolecular charge transfer (TICT). Upon protonation of the dimethylamino groups in BOPIM-dma, its fluorescence was turned on ascribed to the inhibition of TICT. Its emission can be switched 'on' or 'off' between pH 2.4 and 4.0, and it undergoes a reversible protonation-deprotonation reaction wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Currently, it is still a great challenge to develop stable dual‐functional fluorescence sensors for proteins. BOPIM derivatives with electron donor group –PhN(CH 3 ) 2 , BOPIM‐1 and BOPIM‐2 (Scheme ), were previously verified TICT properties and presented pH and polarity‐dependent fluorescence . In the present work, the binding characteristics between BOPIMs and BSA are studied.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Currently, it is still a great challenge to develop stable dual‐functional fluorescence sensors for proteins. BOPIM derivatives with electron donor group –PhN(CH 3 ) 2 , BOPIM‐1 and BOPIM‐2 (Scheme ), were previously verified TICT properties and presented pH and polarity‐dependent fluorescence . In the present work, the binding characteristics between BOPIMs and BSA are studied.…”
Section: Introductionmentioning
confidence: 71%
“…BOPIMs are almost non‐fluorescent in PBS buffer when excited at 365 nm because of TICT effect . For BOPIM‐1 (2.0 μ m ), only a weak emission at 518 nm is observed (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…[16] Shen et al analyzed BOPIM-DMA and, it was found that the emission of the molecule changed between pH 2.4-4.0 as "on" and "off" and the pKa was calculated as 3.12. [17] While the interaction of BOPIM-dma with many cations in aqueous systems was examined by Ping et al in 2015, [18] Liu et al in 2017 showed that BOPIM-DMA, an innovative fluorophore, was a sensitive probe for bovine serum albumin (BSA). [19] Both in vivo and in vitro studies of BOPIM derivatives were carried out by Chen for the first time, and they showed that the nano form of the BOPIM derivative found in the literature by encapsulating biocompatible poly (PEG/PPG/PLA urethane) has the potential to be used in tumor diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al. analyzed BOPIM‐DMA and, it was found that the emission of the molecule changed between pH 2.4–4.0 as “on” and “off” and the pKa was calculated as 3.12 [17] . While the interaction of BOPIM‐dma with many cations in aqueous systems was examined by Ping et al.…”
Section: Introductionmentioning
confidence: 99%
“…The π-conjugating system bearing free basic nitrogen atoms can undergo significant change in electronic structure upon protonation, thus providing a nice strategy to construct fluorescent MOFs for pH detection . However, the strong coordinative ability of the N sites with metal ions imposes a limitation on the strategy.…”
Section: Introductionmentioning
confidence: 99%